Back Cover: Platinum Overgrowth on Gold Multipod Nanoparticles: Investigation of Synergistic Catalytic Effects in a Bimetallic Nanosystem (ChemNanoMat 3/2017). Issue 3 (21st February 2017) - Moon, Youngseo; Mai, Hien Duy; Yoo, Hyojong
Abstract : Gold multipod nanoparticle (GMN) core—platinum shell nanostructures (GMN@Pt NPs) were successfully synthesized through the overgrowth of Pt on the surface of GMN seeds. Due to the structural uniqueness of GMNs, GMN@Pt NPs show bimetallic core–shell geometries, which have surface roughness and star‐shaped multi‐branches with sharp edges and tips. The thickness of the Pt shell can be readily manipulated by changing the amount of Pt 2+ precursor in the starting solution. The thickness of Pt layers gradually increases with increasing the amount of Pt 2+ precursor in the starting solution, while the original multi‐pod morphologies are well‐sustained. More information can be found in the Full Paper by H. Yoo et al. onpage 196 in Issue 3, 2017 (DOI:10.1002/cnma.201600322 ).